OPTIMIZATION OF WELDED LAP JOINTS, LOADED LONGITUDINAL FORCE ON PROFITABILITY - R.R. KOTLYSHEV (Advanced Engineering Research, 2007)
The results of researching function of cost of welded lap joints are presented. Two lap joints are examined, working both on a tension, and on a squeezing: plate with a plane and corners with a plane. The dependences are deduced for designing welded lap joints with minimal cost. The results of researches can be useful to the designers.